2015
DOI: 10.5812/ircmj.32076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulsed Wave Low-Level Laser Therapy on Tibial Complete Osteotomy Model of Fracture Healing With an Intramedullary Fixation

Abstract: Background:Fractures pose a major worldwide challenge to public health, causing tremendous disability for the society and families. According to recent studies, many in vivo and in vitro experiments have shown the positive effects of PW LLLT on osseous tissue.Objectives:The aim of this study was to evaluate the outcome of infrared pulsed wave low-level laser therapy (PW LLLT) on the fracture healing process in a complete tibial osteotomy in a rat model, which was stabilized by an intramedullary pin.Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…This skewed distribution between treatment groups makes it less likely that the laser treatments improved osteotomy healing. The lack of effect on osteotomy healing supports the findings of another clinical trial in dogs but conflicts with in vivo studies that used rodent models as well as with a clinical trial in man . Many variables can affect bone healing in response to laser therapy, including frequency of application .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This skewed distribution between treatment groups makes it less likely that the laser treatments improved osteotomy healing. The lack of effect on osteotomy healing supports the findings of another clinical trial in dogs but conflicts with in vivo studies that used rodent models as well as with a clinical trial in man . Many variables can affect bone healing in response to laser therapy, including frequency of application .…”
Section: Discussionmentioning
confidence: 80%
“…The lack of effect on osteotomy healing supports the findings of another clinical trial in dogs but conflicts with in vivo studies that used rodent models as well as with a clinical trial in man . Many variables can affect bone healing in response to laser therapy, including frequency of application . Chang, Wu et al demonstrated improved fracture healing in human hand and wrist fractures after 5 treatments per week for 2 weeks .…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that pulsed wave (PW) light therapy can be more effective than continuous wave (CW) light therapy in some biological systems 26–28. To compare the efficacy of PBM therapy on anti‐inflammation activity in the LPS involved host–bacteria interaction model, we examined the cell viability and cytokine productions under low or high pulse frequency conditions (5 or 500 Hz; Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…All rats underwent surgery to produce mid‐diaphyseal fractures of the left tibiae using a previously reported method . The animals were anesthetized with an intraperitoneal injection of 10% chloral hydrate (3.3 ml/kg).…”
Section: Methodsmentioning
confidence: 99%
“…All rats underwent surgery to produce mid-diaphyseal fractures of the left tibiae using a previously reported method. 14,15 The animals were anesthetized with an intraperitoneal injection of 10% chloral hydrate (3.3 ml/kg). A 1-cm incision was made anterior to the upper end of the right tibia through the skin and the subcutaneous tissues, and the tibia plateau was exposed under sterile conditions.…”
Section: Rat Tibia Fracture Modelmentioning
confidence: 99%